Contagious ecthyma: How serious is the disease worldwide? - Lawan, Zaharaddeen; Bala, Jamilu Abubakar; Bukar, Alhaji Modu; Balakrishnan, Krishnan Nair; Mangga, Hassana Kyari; Abdullah, Faez Firdaus Jesse; Mohamed Noordin, Mustapha; Mohd Azmi, Mohd Lila (Cambridge University Press, 2021)
Contagious ecthyma (CE) is an infectious disease of small ruminants caused by a parapoxvirus of family Poxviridae subfamily Chordopoxvirinae. The disease is obviously distinguished by an establishment of scabby lesions and ulcerative formation on less hairy areas including muzzle, ears, nostril, and sometimes on genitalia. The disease is endemic in sheep and goats. The virus is transmissible to other ruminants and is a public health concern in humans. Although the disease is known as self-limiting, it may cause a significant economic threat and financial losses due to lower productivity in livestock production. Information with regard to the risk of the disease and epidemiology in most parts of the world is underreported. This paper aims to provide relevant information about the epidemiology of CE in selected regions of Europe, South America, North America, Asia, Africa, and Australia. An in-depth comprehension of virus infection, diagnoses, and management of the disease will enable farmers, researchers, veterinarians, abattoir workers, health personnel, and border controllers to improve their measures, skills, and effectiveness toward disease prevention and control, toward reducing unnecessary economic loss among farmers. A herd health program for significant improvement in management and productivity of livestock demands a well planned extension program that ought to encourage farmers to equip themselves with adequate skills for animal healthcare.